2022
DOI: 10.2186/jpr.jpr_d_21_00099
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of conventional and implant-retained overdentures on brain activity and cognition in a geriatric population - A functional MRI study

Abstract: This study aims to evaluate the effect of rehabilitation with complete dentures versus implant-retained overdenture on activity in various parts of the brain cognition in a geriatric edentulous population via Functional MRI (fMRI) studies and the Mini-Mental State Examination (MMSE). Methods: Ten completely edentulous patients were rehabilitated with both complete dentures and two-implant retained overdentures for three months each. fMRI studies were performed for each modality during chewing and recall tasks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 39 publications
0
9
0
5
Order By: Relevance
“…Each study recruited approximately 4–20 patients. One study reported details on the sample size calculation [ 23 ], whereas another study simply mentioned that the “sample size was calculated to be seven” [ 24 ]. No study explicitly mentioned the socioeconomic background or ethnicity of the subjects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each study recruited approximately 4–20 patients. One study reported details on the sample size calculation [ 23 ], whereas another study simply mentioned that the “sample size was calculated to be seven” [ 24 ]. No study explicitly mentioned the socioeconomic background or ethnicity of the subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were cross-sectional with between-group comparisons [ 27 , 28 ]. Meanwhile, only three studies collected brain activity data from their patients before the experimental interventions: Two collected data while patients were wearing their old complete dentures [ 23 , 29 ], and one collected data while patients were completely edentulous, without dentures [ 24 ]. Brain activation in response to several tasks was assessed, with the most popular task being jaw (denture teeth) clenching and gum-chewing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This issue of JPR addresses a variety of topics, particularly regarding elderly people, including a study to develop a simple screening test for mastication [4], image analysis to clarify the effects of food particle loss on the evaluation of masticatory ability [5], and finding an association between abnormal masticatory movement and oral/physical function, possibly influenced by central motor control [6]. Interestingly, Padmanabhan et al [7] observed superior sensory feedback and improved cognitive performance in edentulous patients with implant-retained overdentures compared with those with conventional complete dentures. Many Asian countries are now facing a rapidly aging population, where partially edentate patients are increasing in incidence with frailty, cognitive impairment, and mul-tiple chronic diseases [8].…”
Section: Dear Readersmentioning
confidence: 99%